Estilos de vida de los pacientes con insuficiencia renal crónica que reciben hemodiálisis en el Hospital General Puyo. Año 2015. - Navarro Paredes, María José (2015)
This research study was to determine the lifestyles of patients with chronic renal failure receiving hemodialysis Puyo General Hospital. 2015. The design was cross-sectional, descriptive, bibliographic, field. The techniques used were observation and survey your instrument the questionnaire was applied to 45 patients suffering from chronic renal failure of that nursing home. The results allowed to obtain the following demographic characteristics of the study population: patients aged 65 to 89 years are the most in the 48.90%, followed by 40 to 64 with 33.33%. Predominant female population with 53.33%. He referred the mestizo population 86.67%.The 60% are married couples. Regarding occupation, 37.77% reports no activity. 86.67% comes from the urban sector. The educational level reported 57.78% with primary and secondary 24.44%. Patients in the 62.22% reported low economic level. Referring to feed patients are not healthy feed which consume more carbohydrates amount 93.33%, 53.33% physical activity does nothing; recreational activities the 46.69% watch television. As side effects of hemodialysis patients report feeling tired 62.22%, 13.33% weakness. It is concluded that patients with chronic renal failure mostly do not practice healthy lifestyles. As a contribution the author conducted educational activities and demonstration workshops for patients and family.